INVESTIGATION OF WET, BULK, AND DRY DEPOSITION CONCENTRATIONS IN KIRKLARELI, TURKEY - (:unkn) unknown (STEF92 TECHNOLOGY LTD, 2013)
This study presents the chemical composition of wet, bulk, and dry deposition in the urban and in the rural area of Kirklareli city (Turkey) during the period of March 2011 June 2011. During the sampling period, 12 wet, 12 bulk, and 12 dry samples were collected simultaneously in the city center and in the rural area. Concentrations of main cations (Na+, Mg2+, Ca2+, K+, NH4+) and main anions (Cl-, NO3-, SO42-) were determined in wet, bulk, and dry samples; pH was also measured in these three deposition types. Predominant ions were identified. The mean wet deposition concentrations of all ions except K+ sampled in the city center were found to be higher than those of the rural area. The average pH values of the wet deposition in the urban and the rural area of Kirklareli city were found 6.53 and 6.45, respectively. The study showed that Ca2+ was the dominant cation and SO42- the dominant anion in all deposition samples in the city center. Ion sources in the wet, bulk, and dry depositions were found by calculating the enrichment factors (EFs).
Keywords: rain chemistry; enrichment factor; PRECIPITATION